1992
DOI: 10.1182/blood.v80.12.3044.3044
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro stem cell function of c-kit- and Sca-1-positive murine hematopoietic cells

Abstract: c-kit is expressed on hematopoietic stem cells and progenitor cells, but not on lymphohematopoietic differentiated cells. Lineage marker- negative, c-kit-positive (Lin-c-kit+) bone marrow cells were fractionated by means of Ly6A/E or Sca-1 expression. Lin-c-kit+Sca-1+ cells, which consisted of 0.08% of bone marrow nucleated cells, did not contain day-8 colony-forming units-spleen (CFU-S), but 80% were day-12 CFU-S. One hundred cells rescued the lethally irradiated mice and reconstituted hematopoiesis. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
125
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(136 citation statements)
references
References 20 publications
6
125
0
5
Order By: Relevance
“…As shown in Figure 1, the lin−c‐kit+Sca‐1+ cell population in the bone marrow of control mice was very small. Similar observations have been reported in C57BL/6 mice previously [22]. However, the number of lin−c‐kit+Sca‐1+ cells in the bone marrow was markedly increased following E. coli infection.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 1, the lin−c‐kit+Sca‐1+ cell population in the bone marrow of control mice was very small. Similar observations have been reported in C57BL/6 mice previously [22]. However, the number of lin−c‐kit+Sca‐1+ cells in the bone marrow was markedly increased following E. coli infection.…”
Section: Resultssupporting
confidence: 90%
“…challenge with Escherichia coli . Previous studies have shown that C57BL/6 mouse bone marrow lineage (lin)−c‐kit+Sca‐1+ cells are highly purified (or enriched) hematopoietic stem cells, whereas lin−c‐kit+Sca‐1− cells contain more committed progenitors [22, 23]. Similarly, in Balb/c and FVB/N mouse strains, colony‐forming unit (CFU)‐spleen cells express high levels of the Sca‐1 antigen [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem/progenitor cells (HSCs) undergo self‐renewal and differentiation into all types of blood cells throughout life and have been identified in the lineage‐negative (Lin − )/stem cell antigen‐1‐positive (Sca‐1 + )/c‐Kit + (LSK) population that comprises only 0.05%–0.08% of the murine bone marrow (BM) cells [23, –25]. Differentiation and self‐renewal of HSCs are strictly regulated by various feedback mechanisms to maintain homeostasis of the blood system.…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation studies with injection of HSCs into myeloablated recipients allow for the analysis of the presence of donor cells and their capacity to proliferate and repopulate, thereby indicating HSC activity [1]. In these animal models, murine HSCs have been demonstrated to be negative for lineage markers (Lin − ), including myeloid and B and T cell lineages, and positive for c‐kit, Sca‐1, and CD34 [15].…”
Section: Introductionmentioning
confidence: 99%